The effect of Black Plastic Mulch on Growth, Production and Root Development of Chenin blanc Vines under dryland conditions - Van Der Westhuizen, J. H. (South African Journal of Enology and Viticulture, 2017)
Studies have shown that black plastic used as a mulch at’ planting time under conditions of limited or no irrigation, greatly increased the growth of the vines. Although the exposed plastic film deteriorated within two years, the favourable effect persisted to the fifth year after planting, bringing the mulched vines to production a year earlier than the unmulched vines. The advantages of plastic mulch are conservation of soil moisture, more uniform soil temperatures, weed control and less soil compaction. These factors increase root and shoot growth, and improve both survival of the young vines and production. The durability of the plastic film was extended by covering it with a layer of soil, and thus a longer period of weed control was obtained.